THE TEACHER AS A REFLECTIVE PRACTITIONER: A QUALITATIVE DESCRIPTIVE CASE STUDY OF TEACHING GRADE 4 IN A PROVINCE OF INDONESIA - Wiputra Cendana (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2020)
The purpose of this classroom action research was to see the significance of self-reflection. This reflection is useful to improve teaching practice of having a character to affect students’ learning. This classroom action research took place in one of the private schools in Makassar, South Sulawesi province. The action research was done within a classroom that consists of 22 grade 4 students. The writer used three cycles to describe the progressive growth of both the writer and the students. For gathering data, the writer used several instruments such as documentation (lesson plans, feedback on lessons, and video recording), the writer’s reflection, students’ grade reports, students’ letters and a practicum portfolio. Through the use of the writer’s self-reflection during this practicum, the writer realized that self-reflection helps the writer to improve his way of thinking and acting in his teaching practice. Keywords:Reflection, Teacher, classroom action research